2019
DOI: 10.1017/jfm.2019.422
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation analysis and frequency prediction in shear-driven cavity flow

Abstract: A comprehensive study of the two-dimensional incompressible shear-driven flow in an open square cavity is carried out. Two successive bifurcations lead to two limit cycles with different frequencies and different numbers of structures which propagate along the top of the cavity and circulate in its interior. A branch of quasi-periodic states produced by secondary Hopf bifurcations transfers the stability from one limit cycle to the other. A full analysis of this scenario is obtained by means of nonlinear simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…2017) or edge-state tracking (Bengana et al. 2019), or the use of continuation techniques, such as harmonic balance (Fabre et al. 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2017) or edge-state tracking (Bengana et al. 2019), or the use of continuation techniques, such as harmonic balance (Fabre et al. 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Unstable limit cycles are not easy to track, since they require stabilisation techniques, such as BoostConv (Citro et al 2017) or edge-state tracking (Bengana et al 2019), or the use of continuation techniques, such as harmonic balance (Fabre et al 2019). Alternatively, we have performed a multiple-scale analysis up to fifth order (see appendix C).…”
Section: Weakly Nonlinear Analysismentioning
confidence: 99%
“…12a. A Floquet analysis [26] shows that above a second critical Reynolds number, this flow is in turn destabilized via a Floquet mode with a complex Floquet exponent, as shown in Fig. 12b.…”
Section: Linear Stability Analysismentioning
confidence: 96%
“…Which modes are selected from the discrete set of frequencies however could not be determined by their analysis. Reference [15] very recently showed that in the squared cavity two successive bifurcations lead to two limit cycles with different frequencies and different numbers of structures which propagate along the top of the cavity and circulate in its interior. In contrast, Ref.…”
Section: Introductionmentioning
confidence: 99%